Rhizosphere to rhizosphere hybridization in fruit crops: new perspectives - Srivastava, A. K.; Mousavi, Seyed Majid; Bora, Popy; Hota, Debashish; Pandey, Vikramaditya; Malhotra, S. K.; Ziogas, Vasileios (Frontiers in Horticulture, 2025)
The rhizosphere is a dynamic environment in which multiple microbial activities elicit phenotypical, physiological, and molecular crop responses. For a better understanding of the rhizosphere microbiome, researchers are utilizing next-generation sequencing to focus on microbiome regulations with an emphasis on multi-functional microbes. There are two main concepts currently being focused on: identifying microbial antagonists (between beneficial microbes and plant pathogens) from predominant stocks of plant-growth-promoting microbes, preferably with an aim towards bioprospecting soil-plant health; and secondly, developing a more microbially active rhizosphere through a process called rhizosphere hybridization (RH). The present review is focused on some recent studies on the outcome of RH in citrus cultivars, showing renewed functional corridors of the rhizosphere characterized by secondary metabolites providing a load-supporting functional dichotomy through elevated nutrient-supply, activated soil enzyme profiles, and improvements in root- shoot systems and plant defense enzymes. These response trade-offs collectively contributed to higher quality yield coupled with possibly a better shelf life of fruits. The rhizobiome of heritage trees viz., Azadirachta, Ficus, Dendrocalamus, Populus, Sasa, Acer, Alnus, Quercus, and Phyllostachys, could be effectively used in exercising RH. These observations on RH mean the concept could be expanded in other fruit crops, with an emphasis on developing a robust holobiont (climate-smart suppressive soils and engineering rhizosphere microbiomes for microbially engineered plants) as a part of regenerative agriculture.